P-90 Addressing health inequalities: Implementation of an ethnic minority support worker project. (19th November 2022) - Powell, Emma; Evans, Tricia; McKinnon, Dee
Abstract : Introduction: Compton Care's Clinical Services Strategy identified the need to engage with patients and families from Ethnic Minority communities to address health inequalities. This project is being delivered in partnership with Royal Wolverhampton Trust (RWT), to improve support to patients with complex and incurable conditions from Ethnic Minority communities. Aim: This project aims to provide a key link for patients/families to help navigate the health system and access care and support. Methods: Funding was secured from NHS Charities Together. Funding is being used to provide further reach and extend Compton's palliative care services into a larger population of Wolverhampton's community, helping to address some of the inequalities of care experienced by people from ethnically diverse backgrounds (Szczepura, 2005. Postgraduate Medical Journal. 81: 141). An Ethnic Minority Support Worker was employed in March 2022, taking referrals from Royal Wolverhampton Trust Community Nurses and Compton teams. Evaluation is via a patient/family member completed electronic form and asks for self-rating how they feel their needs were met in areas including information delivery and access to services. Results: The support worker has signposted to external services, referred to Compton services, facilitated family discussions, given emotional support and practical help (e.g., finances, accessing social care). At present 21 individuals have received support. By identifying and contacting patients early in their diagnosis, we maximise the amount of support which can be offered. Creation of an electronic system has supported the rapid identification of potential patients and family members. This has run for 7 days and already 10 patients have been flagged and will be onboarded to the service. None of these individuals were aware that Compton could assist them with their needs. Discussion: The project has recently started and is already having an impact. Further collection of broader activity data and completion of case studies during the remainder of the project will contribute to a fuller picture.